Effects of freeze-thaw dynamics and microplastics on the distribution of antibiotic resistance genes in soil aggregates. (July 2023) - Xu, Fukai; Guan, Jiunian; Zhou, Yumei; Song, Ziwei; Shen, Yanping; Liu, Yibo; Jia, Xiaohui; Zhang, Baiyu; Guo, Ping
Abstract: This is the first study investigating the effects of freeze-thaw (FT) and microplastics (MPs) on the distribution of antibiotic resistance genes (ARGs) in soil aggregates (i.e., soil basic constituent and functional unit) via microcosm experiments. The results showed that FT significantly increased the total relative abundance of target ARGs in different aggregates due to the increase in intI1 and ARG host bacteria. However, polyethylene MPs (PE-MPs) hindered the increase in ARG abundance caused by FT. The host bacteria carrying ARGs and intI1 varied with aggregate size, and the highest number of hosts was observed in micro-aggregates (<0.25 mm). FT and MPs altered host bacteria abundance by affecting aggregate physicochemical properties and bacterial community and enhanced multiple antibiotic resistance via vertical gene transfer. Although the dominant factors affecting ARGs varied with aggregate size, intI1 was a co-dominant factor in various-sized aggregates. Furthermore, other than ARGs, FT, PE-MPs, and their integration promoted the proliferation of human pathogenic bacteria in aggregates. These findings suggested that FT and its integration with MPs significantly affected ARG distribution in soil aggregates. They amplified antibiotic resistance environmental risks, contributing to a profound understanding of soil antibiotic resistance in the boreal region. Graphical abstract: Image 1 Highlights: Effects of FT and MPs on ARG distribution in soil aggregates were investigated. ARG increase in aggregates under FT was due to elevated intI1 and potential hosts. FT and MPs enhanced antibiotic resistance via vertical gene transfer. intI1 was the common factor affecting ARG abundance in different-sized aggregates. FT, PE-MPs, and their integration promoted the proliferation of HPB in aggregates.